Behavior of beam-column joints with high performance fiber-reinforced concrete under cyclic loading. (October 2022) - Wang, Dehong; Zhao, Jian; Ju, Yanzhong; Shen, Hao; Li, Xiaozhou
Abstract: A total of eight interior beam-column joints with high performance fiber-reinforced concrete (HPFRC) were fabricated and tested to investigate their seismic behaviors in terms of failure mode and load-carrying capacity. The effects of stirrup ratio in the joint zone, strength of reinforcement in the beam, axial compression load level, web reinforcing bars, and vertical reinforcing bars across the joint zone on the shear capacity of HPFRC beam–column joints were analyzed. A formula for calculating ultimate shear strength of HPFRC joints was established. It was demonstrated that interior beam-column joints with HPFRC have good load-carrying capacity, which were attributed to the superior mechanical properties of the HPFRC. After cracking, the tensile strain of the stirrups increased in the middle of the vertical length of the joint and decreased in the upper and lower parts. The ultimate bearing capacity of the specimen increased by 11.1% when the column axial load increased from 0.3 fc Ac to 0.5 fc Ac (where fc is the compressive strength and A c is the column area). However, when the column axial load increased from 0.5 fc Ac to 0.6 fc Ac, the ultimate bearing capacity of the specimen is almost unchanged. The stirrup ratio of the joint zone increased from 0 to 2.90%, and the ultimate bearing capacity of the joint increased by 21.34%. The non-corner vertical reinforcement in columns and the stirrups in joint zone improve the load-carrying capacity of beam-column joints with HPFRC.